Using Intelligent Educational technology in Computer Network - Beheshti, Mobina; Pakfar, Amir (Elsevier Science Bv, 2014)
Nowadays distance learning has become very popular. The need for fully adaptive, intelligent tutoring systems has all the time developed. Artificial intelligence (AI) techniques applied to education to reveal the aim of existing tutors and provide better appreciation of this useful field. The dimensions for intelligent tutoring system (ITS) have studied to adapt the teaching according to examining the major knowledge structures required for an IT'S: knowledge area, instructional information, communication knowledge, and user knowledge. This paper is about learning network principle by intelligent system. The proposed method intended is to give a pretest exam to users for measuring knowledge level, following by accessing to the learning area, and at the end passing posttest exam to evaluating the improvement level. In this system, we proposed Network tutoring intelligent system that utilizes PHP programming for designing intelligent education system, My-SQL database for recording data, and fuzzy method to evaluate user knowledge level and degree of improvement by giving pretest and posttest quizzes. (C) 2013 The Authors. Published by Elsevier Ltd. Selection and/or peer-review under responsibility of Academic World Education and Research Center.
5th World Conference on Educational Sciences (WCES) -- FEB 05-08, 2013 -- Rome Sapienza Univ, Rome, ITALY
Keywords: training intelligent; knowledge level; better appreciation; aim of existing